New or poorly known Douglasiidae from the Palaearctics (Lepidoptera: Douglasiidae) - R. Gaedike (SHILAP)
Five new species of the genus Tinagma Zeller, 1839 were described and illustrated (T. fasciatum Gaedike, sp. n., T. mikkolai Gaedike, sp. n., T. jalavai Gaedike, sp. n., T. kullbergi Gaedike, sp. n., T. caucasicum Gaedike, sp. n.). New country records for five species of the same genus (T. perdicella Zeller, 1839, T. balteolella (Fischer von Röslerstamm, 1841), T. klimeschi Gaedike, 1987, T. bledella (Chrétien, 1915), T. ocnerostomella (Stainton, 1850)) and for two species of the genus Klimeschia Amsel, 1938 (K. transversella (Zeller, 1839), K. cinereipunctella (Turati & Fiori, 1930) are provided.